Origin of purple asparagus cultivar ‘Pacific Purple’ based on the sequence of sex determination gene - Kanno, Akira; Hirobe, Nana; Zhang, Lei (Frontiers in Plant Science, 2023)
Garden asparagus is one of the most important crops worldwide. Since this crop is dioecious and male plants generally have higher yields compared to female plants, several DNA markers for sex identification have been developed for acceleration of asparagus breeding. Among these markers, Asp1-T7sp and MSSTS710 were found to be effective in sex determination for many asparagus cultivars. However, we previously found that these markers were not completely suitable for sex identification in the purple asparagus cultivar 'Pacific Purple'. There are two types of male individuals in this cultivar: One type is PP-m, which is identified the sex type by Asp1-T7sp and MSSTS710 markers, while the other type is PP-m* whose sex type is not identified by these markers. Since the sex identification markers are located on the non-recombining Y region, it was expected that the sequence around this region might be different between PP-m and PP-m*. In this study, the sequence of one of the sex-determining genes, MSE1/AoMYB35/AspTDF1, was analyzed, and a comparative analysis was conducted among PP-m and PP-m* of 'Pacific Purple', A. officinalis and related species A. maritimus. The results revealed that PP-m and PP-m* has the similar sequence of MSE1/AoMYB35/AspTDF1 gene from A. officinalis and A. maritimus, respectively. 'Pacific Purple' is a cultivar developed through polycross hybrid from Italian landrace 'Violetto d'Albenga' (VA), suggesting that VA originated from an interspecific crossing between A. officinalis and A. maritimus and that the pollen parent used in 'Pacific Purple' breeding contained two types of male individuals with different MSE1/AoMYB35/AspTDF1 sequence. As a result, PP-m and PP-m* of 'Pacific Purple' harbors the similar sequences of the MSE1/AoMYB35/AspTDF1 gene from A. officinalis and A. maritimus, respectively.